Expression of Transforming Growth Factor-beta 1 (TGF-β1) in the Developing Periodontium of Rats - Gao, J.; Symons, A.L.; Bartold, P.M. (Journal of dental research, 1998)
Transforming growth factor-beta 1 (TGF-pl) has been reported to be expressed within several tissue compartments of developing molar crowns and therefore is implicated in tooth development. Additionally, TGF-β1 may also play a crucial role in tissue repair and regeneration. The aim of this study was to determine the distribution of TGF-β1 in the developing periodontal attachment apparatus (cementum, periodontal ligament, and alveolar bone) in Lewis rats. Animals aged 3, 6, and 12 wks were killed, their mandibles removed, fixed, demineralized, and processed in paraffin. The localization of TGF-β1 in tissues was detected by polyclonal goat antibodies against human TGF-pl by means of immunoperoxidase techniques. TGF-β1 messenger RNA was detected by in situ hybridization with a cocktail oligonucleotide probe. Cell counts were determined for analysis of the percentage of cells stained positive for TGF-β1. Results revealed that TGF-β1 was expressed in the developing alveolar bone, periodontal ligament, and cementum at all stages of tissue development studied. Staining was stronger at sites of cementum and alveolar bone compared with the periodontal ligament. Intensity of the positive staining, based on 3 grades, indicated a similarity between the tissues obtained from different ages, but varied between several cell types. Cementoblasts and osteoblasts stained more strongly than fibroblasts. Large numbers (- 90%) of the osteocytes in developing bone expressed TGF-β1; however, in mature bone, fewer osteocytes stained for TGF-β1. The percentages of positively stained cementoblasts, osteoblasts, and fibroblasts in the periodontal space were greater at the apical portion than at the cervical portion of the root. TGF-β1 mRNA was expressed in osteoblasts, some bone marrow cells, cementoblasts, and fibroblasts. This study indicates that TGF-β1 may play an important role in the modulation of tissue formation and development of the periodontium.